2011
DOI: 10.1007/s12576-011-0146-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-related change in the effect of gentle mechanical cutaneous stimulation on the somato-cardiac sympathetic C-reflex

Abstract: This study examined whether aging influences the effect of gentle mechanical cutaneous stimulation (touch) on somato-cardiac sympathetic reflexes in anesthetized rats. A single electrical stimulus (15 V, 0.5 ms) applied to the tibial nerve induced somato-cardiac sympathetic A- and C-reflexes, which originated from the myelinated A- and unmyelinated C-fibers of the tibial nerve, respectively. When touch was applied to the inner thigh ipsilateral to the electrical stimulation, the C-reflex was selectively inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In addition, according to Gibbs et al [ 27 ], the frequency of bradycardiac and depressor response increases when the concentration of inhalation anesthetics becomes higher. Thus, it was assumed that bradycardiac responses were more likely to be caused due to experimental conditions in the present study (noxious heat stimulation applied to the lower back and rumps and deeper anesthesia than conventional depth [ 8 , 9 ]). A difference in cardiovascular responses to noxious stimulation (bradycardia or tachycardia) was assumed to be centrally mediated [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, according to Gibbs et al [ 27 ], the frequency of bradycardiac and depressor response increases when the concentration of inhalation anesthetics becomes higher. Thus, it was assumed that bradycardiac responses were more likely to be caused due to experimental conditions in the present study (noxious heat stimulation applied to the lower back and rumps and deeper anesthesia than conventional depth [ 8 , 9 ]). A difference in cardiovascular responses to noxious stimulation (bradycardia or tachycardia) was assumed to be centrally mediated [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The preparatory surgery was described previously [ 8 , 9 ]. In brief, the carotid artery and jugular vein were catheterized for continuous arterial blood pressure recording and administration of anesthetics and supplemental fluids, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural stimulation such as gentle touch is able to activate these non-noxious nerve fibers without noxious fiber activation. While little is known about the physiological functions of low-threshold mechanoreceptive Aδ and C fibers, we found that these afferents may contribute to autonomic regulation (Hotta et al, 2010(Hotta et al, , 2018Watanabe et al, 2011Watanabe et al, , 2015. In the following section, the effects of natural stimulation (gentle stimulation) on urinary bladder function are introduced.…”
Section: Effects Of Somatic Electrical Stimulation On the Micturitionmentioning
confidence: 99%